Osteomyelitis: epidemiological analysis of the disease in Sergipe - Hora, Menandro Araujo Chantel (2023)
Osteomyelitis is an infection that affects the bone and can lead to destruction of this tissue. It is important due to its relevant complications for patients. To analyze the epidemiological profile of patients affected by osteomyelitis in Sergipe from January 2012 to December 2021. Descriptive cross-sectional study, through the collection of information in the Department of Informatics of the SUS (DATASUS), based on data from the Hospital Information System of the Unified Health System – SIH/SUS during the years 2012 to 2021. Data were recorded and analyzed in a Microsoft Office Excel spreadsheet (2010 version). During the years 2012 to 2021 in Sergipe there were 1,746 hospitalizations for osteomyelitis in Sergipe. There were 1255 hospitalized men and 491 women in the studied period. The average amount spent per hospitalization in the total period studied was R$961.79. The age group with the highest number of hospitalizations was from 30 to 39 years old. Sergipe registered 71 deaths and a mortality rate of 4.07 in the studied period. The male gender and age group between 30 and 39 years old were found to be at higher risk. The municipality and hospital with the highest number of admissions was Aracaju and HUSE, respectively. The average cost per hospitalization was lower in Sergipe, when compared to Brazil and the Northeast region. Sergipe had the highest national mortality rate for the period studied. Having identified the risk factors and epidemiological profile of the disease in Sergipe, it is necessary to implement public health policies aimed at caring for male patients, young adults (30 to 39 years old), diabetics and victims of exposed fractures.